Combining clinical markers can predict mortality in NYHA IV heart failure - Yi-jiao Men; Yan-ling Dong; Yu Gong; Ya-qing An; Hong-bo Cheng (Scientific Reports)
Abstract Early assessment of heart failure during treatment can improve patient prognosis. Brain natriuretic peptide (BNP), uric acid (UA), pre-albumin (PA), red blood cell distribution width (RDW), and Cystatin C (Cys C) are related to the development of heart failure. This study determined whether these characteristics could serve as combined diagnostic indicators for the prognosis of New York Heart Association classification (NYHA) IV heart failure (IV-HF). Here, the general clinical and cardiac ultrasound data from 193 patients with NYHA IV-HF were collected and followed-up for six months, and their survival status was recorded. Among the patients, 119 (61.66%) survived, whereas 74 (38.34%) were reported dead at the six-month follow-up. Compared to the survival group, the death group had significantly higher age, disease duration, Cys C, UA, BNP, RDW, left ventricular end-systolic diameter, left ventricular end-diastolic diameter, and left atrial dimension, and lower PA and left ventricular ejection fraction (LVEF). Cys C, UA, BNP, and RDW had significant negative linear correlations with LVEF, while PA had a significant positive linear correlation with LVEF. In addition, high Cys C, UA, BNP, and RDW, as well as low PA, are independent risk factors for mortality in patients with IV-HF. The combination of age, disease duration, RDW, and levels of Cys C, UA, BNP, and PA can serve as diagnostic indicators for mortality in patients with NYHA IV-HF.